Procuring Survival - Matilde Cappelletti; Leonardo M. Giuffrida; Gabriele Rovigatti (Center for Economic Studies and ifo Institute (CESifo), 2022)
We investigate the impact of public procurement spending on business survival. Using Italy as a laboratory, we construct a large-scale dataset on firms–covering balance-sheet, income-statement, and administrative records–and match it with public contract data. Employing a regression discontinuity design for close-call procurement auctions, we find that winners are more likely to stay in the market than marginal losers after the award and that the boost in survival chances lasts longer than the contract duration. We document that this effect is associated with earnings substitution rather than increased business scale. Regardless of size, contracts that are long-lasting and awarded by decentralized buyers are more impactful for survival prospects. Survivors experience no productivity premium but rather an improvement in their credit position.
Keywords: D25; D44; H32; H57; 330; firm survival; firm dynamics; public demand; public procurement; demand shocks; productivity; credit; auctions; regression discontinuity design